Conservative treatment for hypervascularised placental polyp with secondary haemoperitoneum: a case report. - Di Serio, Maurizio; Capozzi, Vito Andrea; Berretta, Roberto; Marcato, Carla; Frusca, Tiziana (Acta Biomedica Atenei Parmensis, 2021)
Objective: We describe the first case to our knowledge of Hypervascularised placental polyp (HPP) presenting with acute pelvic pain and hemoperitoneum. Case Report: A 33 years-old woman with a history of medical abortion three months earlier came to our attention complaining acute pelvic pain and vaginal bleeding. Transvaginal (TV) and transabdominal (TA) ultrasound (US) demonstrated a highly vascular intrauterine lesion and intra-abdominal free fluid consistent with a diagnosis of haemoperitoneum. Emergency laparoscopy yielded no intra-abdominal bleeding and was followed by bilateral selective embolization of the uterine arteries due to persistent vaginal bleeding. Hysteroscopy and pathology findings were consistent with a final diagnosis of HPP. Conclusion: HPP may occur months or years after pregnancy or abortion and the clinical picture of abnormal vaginal bleeding associated with acute abdominal pain and haemoperitoneum should warrant to consider HPP among the differential diagnosis. Clinical and imaging findings need to be considered when planning the conservative management of HPP. Our experience suggests that uterine artery embolization is a safe and effective for the conservative treatment of highly vascularized HPP.